2020
DOI: 10.1108/josm-04-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Whose experience is it anyway? Toward a constructive engagement of tensions in patient-centered health care

Abstract: PurposeHealthcare delivery faces increasing pressure to move from a provider-centered approach to become more consumer-driven and patient-centered. However, many of the actions taken by clinicians, patients and organizations fail to achieve that aim. This paper aims to take a paradox-based perspective to explore five specific tensions that emerge from this shift and provides implications for patient experience research and practice.Design/methodology/approachThis paper uses a conceptual approach that synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 143 publications
0
30
0
Order By: Relevance
“…Understanding the patient perspective and providing what they need will help the hospitals win the business (Hehenkamp & Kaarbøe, 2020;Miao, Zhang, Wu, Zhang, & Jiang, 2019). For the long run, a strategic value approach is necessary to allow the hospitals to provide more effective and efficient services for improved performance (Porter & Lee, 2021;Vogus, Gallan, Rathert, El-Manstrly, & Strong, 2020). The hospital management must ensure that quality services are provided according to government standards and optimally delivered ( Chakraborty, Kaynak, & Pagán, 2021;Gao & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the patient perspective and providing what they need will help the hospitals win the business (Hehenkamp & Kaarbøe, 2020;Miao, Zhang, Wu, Zhang, & Jiang, 2019). For the long run, a strategic value approach is necessary to allow the hospitals to provide more effective and efficient services for improved performance (Porter & Lee, 2021;Vogus, Gallan, Rathert, El-Manstrly, & Strong, 2020). The hospital management must ensure that quality services are provided according to government standards and optimally delivered ( Chakraborty, Kaynak, & Pagán, 2021;Gao & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The patients become experts when the treatment practice is oriented towards patient involvement and shared decision making. Other studies have also suggested that clinicians may find that patient involvement challenges their expertise as professionals [ 23 , 34 , 76 , 77 ]. This may contribute to explaining this study’s findings, suggesting that clinicians’ perceptions of mastery of work seemed to be influenced by inpatient involvement at their facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as high workload [ 8 ], rapid turnover [ 19 , 20 ], and low social support among the employees [ 5 , 21 , 22 ] have been associated with lower work-related satisfaction in SUD and mental health services. Additionally, conflicting expectations between inpatient and employers may burden healthcare clinicians and influence their work-related satisfaction adversely [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, monitored patients gain better guarantees of safety and autonomy, which reduces their hospital visits; they engage more in their own health protection and display enhanced psychological capabilities. Rather than being passive subjects, they become informed, aware and active, with the power to monitor and understand their health at any time and in any place (Vogus et al, 2020). Through such patient engagement, satisfaction increases, as do opportunities for action.…”
Section: Discussionmentioning
confidence: 99%
“…It also determines the type of relationship that the patient can establish with other members of the health system, across different phases of the healthcare journey. That is, the work of being a patient includes making lifestyle changes, managing medications and other activities with significant cognitive demands, for both patients and their families (Vogus et al, 2020).…”
Section: Patient Engagementmentioning
confidence: 99%